Linking wading bird prey selection to number of nests. Issue 8 (3rd September 2016) - Klassen, Jessica A.; Gawlik, Dale E.; Frederick, Peter C.
ABSTRACT: Establishing a link between food availability and productivity is often central to the recovery of declining populations; however, differences in prey selection may influence how populations are affected by changes in prey availability. We determined prey selection and prey availability for 3 wading bird species, and investigated the effects of prey availability on the number of nests initiated by 6 wading bird species in the Florida Everglades, USA. To determine prey selection, we compared food items recovered from tricolored heron ( Egretta tricolor ), snowy egret ( Egretta thula ), and little blue heron ( Egretta caerulea ) nestlings to aquatic prey availability from throw‐traps across the Everglades landscape from 2012 to 2014. Tricolored heron and snowy egret prey composition was statistically similar across years, with the majority of prey biomass coming from relatively large (>1.9 cm) marsh fish. Little blue heron prey composition differed from the other wading bird species, and contained a higher percentage of grass shrimp ( Palaemonetes paludosus ) and exotic fish species. Numbers of small heron nests were positively influenced by the availability of large marsh fish across the landscape, whereas numbers of nests for other wading bird species (wood stork [ Mycteria americana ], great egret [ Ardea alba ], white ibis [ Eudocimus albus ]) were not. Our results suggest differences among wading bird species in their prey selection and availability. Although small heron foraging may seem restricted by their specialization on marsh fishes, their short nesting cycles allow for the phenological flexibility to delay nesting until foraging conditions are optimal. Conversely, wood storks with longer nesting cycles are more temporally constrained but have greater flexibility in prey items and foraging range. The annual number of small heron nests may be more robust to hydrological variability as a result of management action or global change than the number of wood stork nests. The temporal constraints of nesting by wood storks indicate that management of supporting wetland systems should provide continuous habitat availability during the nesting season. © 2016 The Wildlife Society.